Authorities and options for funding USSOCOM operations - Loredo, Elvira N.; Peters, John E., 1947-; Stanley, Karlyn D.; Boyer, Matthew E.; Welser, William, IV; Szayna, Thomas S., 1960- (Rand Corporation, 2014)
This report examines mechanisms, sources, and inter-Service agreements for funding special operations forces (SOF) operations and provides recommendations to reduce the frequency and duration of disputes between the United States Special Operations Command (SOCOM), the Military Departments, and Geographic Combatant Commands over their respective funding responsibilities for SOF, especially with respect to when Service Common (Major Force Program (MFP) 2) and SOF Peculiar (MFP 11) funds should be used. The Geographic Combatant Commanders, in accordance with guidance received from the President and Secretary of Defense, generate requests for unplanned activities and operations, sometimes in response to unanticipated events. Such events fall outside planned and programmed activities, creating validated operational support requirements that are unfunded and/or unbudgeted. Each time this occurs, it leads to prolonged negotiations to work out funding responsibility disputes among a variety of stakeholders to secure the funding necessary to execute the new requirement. SOCOM's Global SOF Network (GSN) envisions increased use of SOF, which would further increase the frequency of such disputes and could be hindered by current funding processes, motivating the research conducted to produce this report. If the President and Congress agree to expand the use of SOF as described by the GSN concept, it would be necessary to increase the flexibility of funding available for validated but unfunded operations. To increase the effectiveness of SOF, the Department of Defense needs funding solutions that are responsive to global events while enabling effective financial stewardship that satisfies the needs of all stakeholders.